Hybrid minimally invasive esophagectomy for cancer: impact on postoperative inflammatory and nutritional status. Issue 8 (1st December 2016) - Scarpa, M.; Cavallin, F.; Saadeh, L. M.; Pinto, E.; Alfieri, R.; Cagol, M.; Da Roit, A.; Pizzolato, E.; Noaro, G.; Pozza, G.; Castoro, C.
Summary: The purpose of this case–control study was to evaluate the impact of hybrid minimally invasive esophagectomy for cancer on surgical stress response and nutritional status. All 34 consecutive patients undergoing hybrid minimally invasive esophagectomy for cancer at our surgical unit between 2008 and 2013 were retrospectively compared with 34 patients undergoing esophagectomy with open gastric tubulization (open), matched for neoadjuvant therapy, pathological stage, gender and age. Demographic data, tumor features and postoperative course (including quality of life and systemic inflammatory and nutritional status) were compared. Postoperative course was similar in terms of complication rate. Length of stay in intensive care unit was shorter in patients undergoing hybrid minimally invasive esophagectomy ( P = 0.002). In the first postoperative day, patients undergoing hybrid minimally invasive esophagectomy had lower C-reactive protein levels ( P = 0.001) and white cell blood count ( P = 0.05), and higher albumin serum level ( P = 0.001). In this group, albumin remained higher also at third ( P = 0.06) and seventh ( P = 0.008) postoperative day, and C-reactive protein resulted lower at third post day ( P = 0.04). Hybrid minimally invasive esophagectomy significantly improved the systemic inflammatory and catabolic response to surgical trauma, contributing to a shorter length of stay in intensive care unit.